Performance of Tropical Cyclone Forecast in Western North Pacific in 2015 - Guomin Chen; Xiaotu Lei; Xiping Zhang; Peiyan Chen; Hui Yu; Rijin Wan (Tropical Cyclone Research and Review, 2016)
ABSTRACT: The operational track and intensity forecast errors of tropical cyclones (TCs) over the western North Pacific in 2015 were evaluated on the basis of RSMC-Tokyo’s “best-track” dataset. The results showed that position errors for each official agency were under 80 km, 130 km, 180 km, 260 km and 370 km at 24, 48, 72, 96 and 120 hr lead time. Stepped decreases in the values of each quantile were made at every lead times and have been made by global models from 2010 to 2015, especially for long lead time. The results of the Track Forecast Integral Deviation (TFID) show a clearly decreasing trend for most global models, indicating that the TC forecast tracks became increasingly similar to the observations. In 2015, the intensity forecast skill scores for both global and regional models were almost negative. However, the skill of EPSs’ intensity forecasting has made significant progress in the past year. Keywords: tropical cyclone, track, intensity, forecast verification, skill scores